Moderate prenatal alcohol exposure impairs cognitive control, but not attention, on a rodent touchscreen continuous performance task. (17th March 2020) - Olguin, Sarah L.; Thompson, Shannon M.; Young, Jared W.; Brigman, Jonathan L.
Abstract: A common feature associated with fetal alcohol spectrum disorders is the inability to concentrate on a specific task while ignoring distractions. Human continuous performance tasks (CPT), measure vigilance and cognitive control simultaneously while these processes are traditionally measured separately in rodents. We recently established a touchscreen 5‐choice CPT (5C‐CPT) that measures vigilance and cognitive control simultaneously by incorporating both target and nontargets and showed it was sensitive to amphetamine‐induced improvement in humans and mice. Here, we examined the effects of moderate prenatal alcohol exposure (PAE) in male and female mice on performance of the 5‐choice serial reaction time task (5‐CSRTT), which contained only target trials, and the 5C‐CPT which incorporated both target and nontarget trials. In addition, we assessed gait and fine motor coordination in behavioral naïve PAE and control animals. We found that on the 5‐CSRTT mice were able to respond to target presentations with similar hit rates regardless of sex or treatment. However, on the 5C‐CPT PAE mice made significantly more false alarm responses vs controls. Compared with control animals, PAE mice had a significantly lower sensitivity index, a measure of ability to discriminate appropriate responses to stimuli types. During 5C‐CPT, female mice, regardless of treatment, also had increased mean latency to respond when correct and omitted more target trials. Gait assessment showed no significant differences in PAE and SAC mice on any measure. These findings suggest that moderate exposure to alcohol during development can have long lasting effects on cognitive control unaffected by gross motor alterations. Abstract :